PENGEMBANGAN MEDIA BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWA MAN 2 BATU MATERI KINGDOM ANIMALIA - Nur’ain, Feni; Chamisijatin, Lise; ., Nurwidodo (University of Muhammadiyah Malang, 2015)
PENGEMBANGAN MEDIA BERBASIS MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN SISWA MAN 2 BATU MATERI KINGDOM ANIMALIA Â Feni Nurâaini1, Lise Chamisijatin1, Nurwidodo1 Â Â Â Â Â Â Â Â Â Â Â 1Pendidikan Biologi FKIP Universtias Muhammadiyah Malang, e-mail : lise_chin@yahoo.com Â ABSTRACT Â Learning biology plays an important role in the educational process as well as the development of technology, because biology has an effort for human to generate interest in science and technology development.Various issues that arise in school in biology learning materials associated with the Kingdom Animalia and the material is very much difficult for students to understand and time limitations in the learning process. So there should be used development of teaching media to overcome this. The purpose of this study are: (1) to know the effectiveness of the implementation of teaching media development, (2) to know the level of students understanding by using the application of teaching media development. This type of research is development research or Research and Development (R & D). the development used is based on the development steps from Borg & Gall (1983) modified from Sukmadinata (2010) which includes three steps, namely: preliminary study, development and validation. To determine the effectiveness of the implementation of teaching media development is done by giving the questionnaire to students. To determine the level of students understanding performed pretest and posttest. The research was conducted on 28 March to 29 September 2013 at MAN 2 Batu Malang. The results of this development in the form of teaching media product Biology that has been through some trials and revisions of the experts and students.Â Based on the feasibility of media experts, subject matter experts, and students teaching media are stated that it is Â Â very viable and effective used in learning. Based on the experimental test on class treatment there was an increasing students understanding of the material of the Kingdom AnimaliaÂ that is the average value before using the media (pretest) increased from 41.60 to 90.3 after using the media (posttest), while the control class average value before reading textbooks (pretest) increased from 48.80 to 68.60 (posttest) after reading the textbooks. Thus it can be stated that teacing media based interaktive multimedia is Â more effective in improving students understanding of X class of MAN 2 Malang on the Kingdom Animalia subject. Â Kata kunci: Animalia kingdom, learning of media, interactive multimedia